Hyporheic ostracods (Crustacea, Ostracoda) from Texas (USA) with six new species - Külköylüoğlu, Okan; Hutchins, Benjamin T.; Yavuzatmaca, Mehmet; Schwartz, Benjamin F. (Zootaxa, 2021)
Between 2015 and 2017, 58 ostracod taxa were collected at 30 locations in 111 samples from the hyporheic zone of surface streams in Texas, U.S.A. Six new species (Bradleycypris foresteri n. sp., Bradleystrandesia macula n. sp., Pseudocandona lordi n. sp., Indocandona rusti n. sp., Stenocypris sancari n. sp., Cyclocypris dalyana n. sp.) are described based on carapace and soft body parts. Additionally, 17 species and two genera (Vestalenula and Indocandona) are presented as new records for Texas, and Indocandona rusti n. sp. is the first record of the genus outside India. Taxonomic positions of the new species are discussed along with ecological information. One-hundred and six nonmarine ostracod species are now reported from Texas. However, ongoing studies suggest that actual species richness is much higher.